Restoration of Electrical Distribution Systems Using a Relaxed Mathematical Model - Souza, Eliane S. [UNESP]; Romero, Ruben [UNESP]; Franco, John F. [UNESP] (Springer, 2018)
This paper proposes a relaxed mathematical model to solve the restoration problem of radial and balanced electrical distribution systems. The mathematical model is a mixed-integer linear programming formulation that can be efficiently solved by commercial solvers. After a restoration problem is solved using this model, the quality and feasibility of the corresponding solution can be verified by using a conventional radial power flow. The performance of the proposed relaxed model is evaluated through exhaustive tests and the solutions found are compared with the ones provided by an exact mathematical formulation. The results obtained demonstrate the efficiency of the proposed approach.
Keywords: Electrical distribution systems; Mathematical programming; Restoration problem